Analysing Drivers’ Preferences for Privacy Enhancing Car-to-Car Communication Systems - (:unkn) unknown (My University, 2020)
While privacy-enhancing solutions for car-to-car communication are increasingly researched, end user aspects of such solutions have not been in the focus. In this paper, we present a qualitative study with 16 car drivers in South Africa for analysing their privacy perceptions and preferences for control and privacy trade-offs, which will allow to derive end user requirements for privacy and identity management for vehicular communication systems. Our results show that while the South African participants are willing to share their location data with family and close friends, they often lack trust in external entities. They perceive safety implications from criminals and hackers and therefore dispel constant location tracking. Usability, privacy and safety are top priorities, with differing privacy – usability trade-offs for different users. The results show that participants demand more control over their privacy and seek usable privacy notices, transparency and fine-grained controls.
Keywords: African Research